An Exploration of the Viability of Forensic Accounting Techniques in Combating Financial Statement Fraud in Nigerian Organizations - Oranefo, Patricia Chinyere; Egbunike, Chinedu Francis (goodwood publishing, 2021)
Purpose: This study explored the viability of forensic accounting techniques in combating financial statement fraud in Nigerian organizations. The study specifically examined the relationship between forensic accounting techniques and fraud deterrence; and, the viability of forensic accounting techniques to enforce corporate policies and procedures. Research methodology: The study adopts the survey research design. The sampling frame comprised accounting lecturers and chartered accountants in two geographical locations of Anambra State. The study utilized non-probability sampling to mitigate non-response bias and to select knowledgeable respondents. The final retrieved questionnaires were fifty. The primary data were analyzed using Pearson correlation analysis. Results: The Pearson correlation results showed a positive association between forensic accounting techniques (FAT) and fraud deterrence. Secondly, there is a positive association between forensic accounting techniques and the enforcement of corporate policies. Limitations: The main limitation was the small sample size from the retrieved questionnaires future studies can therefore widen the sampling frame and explore other sectors. The study also spanned one of the South-eastern States limiting generalizability. Contribution: The study contributes to the literature in the context of developing countries, on the continuing viability of forensic accounting techniques (FAT) in detecting financial statement fraud in its various multifarious forms in such countries with weak institutional environments compared to developed countries. The study also adds to the literature on the viability of forensic accountants in enforcing corporate policies and procedures which is useful in an organizational research context.